PENGEMBANGAN USAHA MANDIRI MASYARAKAT DESA SRIMAHI KECAMATAN TAMBUN UTARA DENGAN PEMANFAATAN LIMBAH SEKAM PADI SEBAGAI CAMPURAN BETON PAVING BLOCK DAN BATAK - Tampubolon, Sudarno P; Lase, Formas Juitan; Sudarwani , Margareta Maria; Sari , Desma; Nataldo , Benny Tri; David , Charly (Universitas Mataram, 2024)
The Community Service Program (PKM) aims to utilize rice husk waste as a mixture in making bricks and paving blocks. Rice husk waste produced from the rice milling process often causes environmental problems. Therefore, through education and training to Zaracon Group Raja Block, through processing rice husk waste into products that have economic value and are environmentally friendly. The methods used include the fabrication of tools, rice husk burning, laboratory testing, socialization, training, and the production of paving blocks using rice husk ash. The results of this program show that paving blocks made using a mixture of rice husk ash have good strength and durability. In addition, this program is also able to improve the skills, insights, and knowledge of the community in processing rice husk waste, so that it can open in business development production of paving block and brick concrete. Keywords: Rice husks, bricks concrete, paving blocks, waste management, community empowerment.